UJI TOKSISITAS ORAL REPEATED DOSE FILTRAT BUAH LUWINGAN (Ficus hispida L.f.) MENGGUNAKAN MODEL TIKUS (Rattus norvegicus Berkenhout, 1769) GALUR WISTAR - Laksmindra Fitria; Rosita Dwi Putri Suranto; Indira Diah Utami; Septy Azizah Puspitasari (BERITA BIOLOGI, 2020)
Hairy fig is a tropical medium-sized tree that produces abundant fruits throughout the year. In some Asian countries, the fruits are consumed as traditional medicine and food ingredient. Meanwhile in Indonesia there has not been much use. A series of oral toxicity tests must be conducted to study the possibility of toxic effects and the safety before further exploration. Oral single dose toxicity study of young and ripe hairy fig fruit filtrate has been carried out. Results demonstrated no observed adverse effect level (NOAEL) at a concentration of 100%. This study was aimed to continue the oral toxicity test with repeated dose following standard toxicity procedure by OECD Test Guideline No. 407 with some modifications. Parameters observed were mortality, sublethal effects consisted of physical conditions and behavior, body weight, core temperature, complete blood count, as well as liver, heart, and renal functions by measuring ALT, AST, and creatinine, respectively. Sampling points on day 0, 7, 14, 21, and 28. Results showed no observed adverse effect level (NOAEL) in both young and ripe fruits filtrate at a concentration of 100% however with a tendency to cause anemia and associate with renal dysfunction. Therefore, it is necessary to perform similar method of toxicity test but with lower concentration, also continue with further toxicity tests (subchronic and chronic periods).